Fate – the Commander's Sergeant: Transformations of the Image of Avenger of the first half of the 20th-cent. Russian poetry referring to the Don Juan myth - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2016)
The aim of this article is to analyze the narrative poem Don Juan by Nikolai Otsup – a poet of the first wave of Russian emigration. Otsup’s work is being compared with the poem The Commander’s Footsteps by Aleksandr Blok and the narrative poem Komandorov’s Footsteps by David Samoilov. The author pays attention to the similarities in poetic images, sound and colouristic symbols. Thanks to the contextualization of Otsup’s narrative poem, the author discovers a common tendency in creating the poetic image of the Commander and in the motif of revenge in the Russian poetry of the first half of the 20th century.